Bank competition and regional integration: Evidence from ASEAN nations - Alexia Ventouri (Review of Development Finance, 2018)
This study provides a characterization of the Association of the South East Asian Nations (ASEAN) banking system's competition under the new environment that the implementation of the Financial Integration Framework (AFIF) implies. We focus on the largest banking markets in the region, represented by the ASEAN-5. The period under study is 2007-2016, covering the preparation period of the ASEAN banks to fully implement the new Banking Integration Framework (ABIF) in 2020. Panzar and Rosse non-structural approach is utilised to measure the competition level. Following Goddard and Wilson's (2009) disequilibrium approach, the test for the dynamic competition measure is also conducted as a robustness check. We examine the evolution of the banking competition by observing the trend of the competition level using a rolling estimation with a 5-year window. This paper also investigates the factors that may influence the competitive conditions, specifically controlling for structural conditions and institutional characteristics. Our main findings confirm that banks operate under monopolistic competition, although there is still a high level of heterogeneity among the ASEAN countries' banking market and banking integration sure is a challenging objective for the region. Our results reveal a positive relationship between density of demand, concentration and competition.
Keywords: G21; L11; N20; 650; ASEAN banking market; Competition; Panzar and Rosse; Disequilibrium approach